INDIGENOUS KNOWLEDGE PRESERVATION OF ORAL LITERATURE “HAHIWANG” IN WEST LAMPUNG - Parangu, Reza Nawafella Alya; Salim, Tamara Adriani (PEOPLE: International Journal of Social Sciences, 2018)
This is a preliminary research that aims to identify the traditional oral literature of hahiwang, and the efforts that have been made in preserving oral literature hahiwang in West Lampung. The method used is qualitative, where the data is collected and analyzed obtained from data collection through observation, and literature review. The result of this research is hahiwang is a traditional oral literature belonging to Krui community, West Lampung. Oral literature of hahiwang is an activity of chanting poem in Lampung with rhythm. The facts, hahiwang oral literature just mastered by the old generation, many young generations know about this oral literature but do not mastered how should its sung. Whereas, the oral literature of hahiwang is full of meaning and moral message about life which is implied from its poem. Some activities of preservation have been done by socialization and externalization.